2022
DOI: 10.21608/adjg.2022.72736.1352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dose Dependent Chemopreventive Effect of Diosmin on Induced Oral Squamous Cell Carcinoma

Abstract: Purpose: This study aimed to evaluate the chemoprevention efficacy of diosmin on experimentally induced hamster buccal pouch (HBP) squamous cell carcinoma utilizing Ki 67 as a proliferative marker. Material and Methods: Seventy Syrian male hamsters were used as experimental animals, these hamsters were divided into five groups, Group I (negative control): 5 hamsters were left untreated. Group II (DMBA treated group): 20 hamsters were divided equally into two subgroups, painted with 0.5% DMBA where subgroup IIa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Additionally, our results revealed significant elevation in the expression of PCNA in the skin of untreated psoriatic rats, indicating an increased level of cell proliferation. Previous studies demonstrated the effect of diosmin of different proliferation markers in different types of cancers such as hepatocellular carcinoma (Tahir et al 2013 ), oral squamous cell carcinoma (Osman et al 2022 ), colon (Zeya et al 2022 ) and gastric cancer (Hu et al 2013 ). Moreover, AKT indirectly induces the transcription of anti-apoptotic genes such as BCL2 via NF-κB factors (Mercurio et al 2021 ; Ozes et al 1999 ; Kane et al 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our results revealed significant elevation in the expression of PCNA in the skin of untreated psoriatic rats, indicating an increased level of cell proliferation. Previous studies demonstrated the effect of diosmin of different proliferation markers in different types of cancers such as hepatocellular carcinoma (Tahir et al 2013 ), oral squamous cell carcinoma (Osman et al 2022 ), colon (Zeya et al 2022 ) and gastric cancer (Hu et al 2013 ). Moreover, AKT indirectly induces the transcription of anti-apoptotic genes such as BCL2 via NF-κB factors (Mercurio et al 2021 ; Ozes et al 1999 ; Kane et al 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study is considered the first study to investigate the efficacy of different diosmin formulations to halt the immune pathogenesis and inflammatory environment of psoriasis. Previous studies reported the anti-inflammatory and immunomodulatory effect of diosmin on the skin keratinocytes in other dermatological diseases such as atopic dermatitis via modulation of Th2 cells activity and the inflammatory cytokines such as IL6 and IL1 (Osman et al 2022 ; Feldo et al 2022 ). In addition, Li et al recently showed that hesperidin, the citrus flavonoid that diosmin is derived from, has the ability to reduce the psoriatic like skin lesions in mice and inhibit the keratinocytes proliferation (Lee et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%